HUBUNGAN TUAK DENGAN TINGGINYA PENDERITA HIPERTENSI DI WILAYAH MEDAN AREA - Aiga Nurkhalilah Pasaribu; Putra Apriadi Siregar (CV. ADIBA AISHA AMIRA, 2024)
The people of North Sumatra, especially the Medanese, are of course very diverse, but the dominant field is filled with the Batak people. This research is qualitative, using secondary data. This study aims to determine the relationship between the behavior of drinking palm wine and the high rate of hypertension sufferers in Kec. Terrain Area. Blood pressure in the body is always related to age and other factors, one of which is the result of consuming alcoholic beverages. Although alcohol can be healthy for the heart, if consumed in excess it will cause dangerous diseases including hypertension. Hypertension is predicted to continue to increase even in 2025 as many as 29 adults are likely to have hypertension